Acute carbohydrate ingestion affects lactate response in highly trained swimmers - Millard-Stafford, M. L.; Brown, M. B.; Snow, T. K. (International Journal of Sports Physiology and Performance, 2010)
Purpose: Effects of acute carbohydrate ingestion on blood lactate (BLa) response to graded exercise was examined in highly trained male and female swimmers. Methods: Twenty-three swimmers performed the United States Swimming Lactate Protocol, a graded interval test (5 × 200 on 5 min), following ingestion of carbohydrate sports drink (CHO) and placebo (PLA). Results: There was no difference in heart rate (P = .55), swim velocity (P = .95), or ratings of perceived exertion (P = .58) between beverages. There was a significant main effect for gender (P = .002) on BLa during all swim stages and recovery. In females, BLa was 27% to 50% higher for CHO during the first (P = .009) and second (P = .04) swim stages. Predicted BLa at selected swim velocity was higher (P = .048) for CHO versus PLA in females at 1.27 m/sand higher (P < .02) for men at 1.4 m/s. Mean (± SD) BLa was significantly (P = .004) greater for CHO (2.7 ± 1.2) compared with PLA (2.0 ± 1.1 mmol/L) during the second test stage and when normalized relative to velocity (P = .004). Peak BLa after the final swim (9.6 ± 3.1 vs. 9.0 ± 3.2 mmol/L, P = .36) was not different between CHO and PLA. Conclusions: Acute CHO ingestion alters the BLa: swim velocity relationship during moderate intensity swims of an incremental swim test, particularly for females. Therefore, pretest beverage ingestion should be standardized during the administration of BLa testing to prevent potential erroneous interpretations regarding athlete`s training status.